Hubungan Tingkat Pengetahuan Gizi dan Asupan Makronutrien terhadap Status Gizi Anggota UKM Bolavoli Universitas Negeri Surabaya - Kinanthi Nur Rachmawati; Anindya Mar’atus Sholikhah; Ratna Candra Dewi; Soni Sulistyarto (Lembaga Pengembangan Kinerja Dosen, 2025)
Good nutritional knowledge can help individuals to consume macronutrient intake in accordance with the body's needs, so that nutritional status can be adequately met. A cross-sectional study design and quantitative research methodology are employed. The study's sample consisted of twenty people who were chosen by purposive sampling. The Spearman rank correlation test was applied in both univariate and bivariate analyses. The results showed that most individuals' nutritional status was normal status (55%). Based on the Spearman rank test, no significant association was identified between nutritional knowledge (p=0.206), protein consumption (p=0.762), and carbohydrate consumption (p=0.772) with nutritional status. Nevertheless, fat consumption (p=0.049) showed a significant link with nutritional status. The results of this research suggest that nutritional status does not correlate with nutritional awareness, protein intake, or carbohydrate intake. However, fat intake is associated with nutritional status. It is intended that this study will inspire participants to practice mindfulness of their macronutrient intake. Coaches are also expected to provide guidance to UNESA volleyball club members to be more discerning in selecting foods for consumption